2018
DOI: 10.18554/refacs.v6i2.2822
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de Burnout em estudantes de Odontologia, Medicina e Enfermagem: uma revisão da literatura

Abstract: O presente estudo tem como objetivo fazer uma revisão integrativa sobre a prevalência e fatores associados ao Burnout em estudantes de Odontologia, Medicina e Enfermagem. Foi realizada busca na base de dados PUBMED, com os descritores: “Burnout syndrome” associados com “dental students”, “medical students “nursing students”, e “health students”, sem restrição de período. As buscas mostraram 22 artigos, os quais, após leitura e seguindo os critérios de inclusão, resultaram em 13 artigos selecionados. A síndrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 15 publications
0
4
0
10
Order By: Relevance
“…QVA-r's goal is to cover the opinions and feelings about the academic environment and daily experiences as an undergraduate student. In addition, it can measure the students' adaptation to several demands of the academic life, as it analyzes interpersonal, academic and contextual (institutional) factors 1 . Validation studies of QVA revealed that the instrument has satisfactory psychometric qualities 1,17,19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…QVA-r's goal is to cover the opinions and feelings about the academic environment and daily experiences as an undergraduate student. In addition, it can measure the students' adaptation to several demands of the academic life, as it analyzes interpersonal, academic and contextual (institutional) factors 1 . Validation studies of QVA revealed that the instrument has satisfactory psychometric qualities 1,17,19 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition to being a progressive process of adaptation, it is multidimensional and complex, strongly dependent on personal and contextual factors. It concerns several dimensions to the students' development that may be affected by variables of academic, social, personal and vocational/professional nature 1,2 .…”
Section: Introductionmentioning
confidence: 99%
“…Diversos fatores podem ser considerados estressores dentro do ambiente universitário, dentre eles, podem-se citar a conciliação entre trabalho e estudo, os acúmulos de avaliações, as pressões psicológicas por notas e o cumprimento de prazos e de período de curso MERCES, 2018;BARLEM et al, 2013;BENAVANTE et al, 2014;FERRAZ;CARDONA;MONTE, 2009;PINTO et al, 2018).…”
Section: Introductionunclassified
“…Além desses supracitados, a SB pode estar associada também a fatores sociodemográficos. Neste trabalho, optou-se por avaliar três aspectos desse tipo de causa, a saber, o sexo MERCES, 2018;CAMPOS et al, 2012;GONÇALVES, 2016;LOPEZ et al, 2017;MEYER, et al, 2012;PINTO et al, 2018), o estado civil (AGUIAR; AGUIAR; MERCES, 2018; GONÇALVES, 2016) e os filhos MERCES, 2018;VIANA et al, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation